MODEL COLLABORATIVE GOVERNANCE DALAM PENANGULANGAN KEMISKINAN DI DAERAH (Studi Kasus dalam Program Dusun Terpadu Mandiri di Boalemo Provinnsi Gorontalo) - Samin Latif (LP2M Universitas Bina Mandiri Gorontalo, 2018)
Poverty is a multidimensional problem that requires integrated handling and involvement of various parties within it. This research has problem formulation was how the collaboration model of government, private and community in poverty reduction through the Dusun Terpadu Mandiri Program in Boalemo, Gorontalo Province. The aim is to explain the role and contribution of the three parties in the poverty reduction through Dusun Terpadu Mandiri program in Boalemo, Gorontalo Province. This research uses case study research with qualitative research design by conducting observations and depth interviews with a number informants and documentation, then analyzed with interactive analysis model. The results of this study found that the collaborative model between government, private and community in the development program of Dusun Terpadu Mandiri (DTM) in Boalemo was done through sharing resources from each party according to the resources and authority possessed through the pioneering and mediation of local government causing this program is more efficient and participative but also a high degree of dependency because of the dominant government intervention. Therefore, this study recommends the need for proactive involvement of the private sector and the community from program planning, implementation and evaluation of its success so that its development and follow-up are more effective